ANALISIS PERKEMBANGAN SUKUK (OBLIGASI SYARIAH) DAN DAMPAKNYA BAGI PASAR MODAL SYARIAH - Kurniawati, Devi Dwi (Jurnal Akuntansi AKUNESA, 2014)
One of the instruments of islamic finance is sukuk (Islamic bonds). Issuance ofislamic bonds in Indonesia has significant development from year to year. But thesignificant growth was not followed by sukuk trading in secunder market. Analysisof the development of the sukuk using descriptive analysis method. Developmentof the sukuk from 2008 through 2012 experienced significant growth year to yearbut a growing amount of sukuk is still small because in 2011 despite a declinesukuk after that progress began to rise and continues to grow. The impact willaffect the development of sukuk islamic capital market regulation to increaseamount of sukuk by the sukuk trading procedures, socialization in improvingunderstanding of sukuk, and the level of investment in the capital markets thataffect the capital market's investment growth. In this case, the development ofsukuk will provide policy direction to be taken by the regulator.Keyword: Sukuk, Investment, Shariah Capital Market.